Intellectual capital efficiency and corporate book value: evidence from Nigerian economy - Anifowose, Mutalib; Abdul Rashid, Hafiz Majdi; Annuar, Hairul Azlan; Ibrahim, Hassan (Emerald Publishing Limited, 2018)
Purpose – The purpose of this paper is to examine the value relevance of intellectual capital (IC) by analysingtherelationshipbetweenICefficiency(ICE)andcorporatebookvalueoflistedfirmsonmainboard of Nigeria Stock Exchange. Design/methodology/approach – This study applies the resource-based theory in formulating two hypotheses that guide the results analysis. By employing a two-step dynamic system generalised method of moments (GMMs), and controlling for the possible endogeneity effect on the parameters estimated, for a sampleof 91 listedfirmson main boardof NigeriaStock Exchange, this studyinvestigates theassociationof ICEandcorporatebookvalue,namely,cashflowfromoperationandeconomicvalueadded(EVA),usingdata over the 2010 to 2014 financial years. Findings – The results show a significant positive relationship between overall ICE and corporate book value (cash flow from operation and EVA). This study contributes to recent evidence concerning the value relevance of IC information to investors and other interested stakeholders. Research limitations/implications – The generalisation of the results to smaller firms, in the alternative securities market, may be inappropriate as study sampled listed firms on the main board of Nigerian Stock Exchange. Practical implications – Those charged with governance should be concerned with the investment and management of IC as it enhances the economic value and operating cash flow in line with the resource-based theory. Originality/value – This study is first to consider the ICE study across all sectors in the Nigerian economy using modified Pulic value added intellectual capital. The study controls for heteroscedasticity and endogeneity issues by adoption of two-step dynamic system GMMs.